2019
DOI: 10.30544/426
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of Mo-Nb microalloyed medium Manganese trip Steel by cyclic quenching

Abstract: A novel cyclic quenching (CQ) and austenite reverse transformation (ART) was proposed for a Fe-0.25C-3.98Mn-1.22Al-0.20Si-0.19Mo-0.03Nb (wt.%) Mo-Nb microalloyed medium-Mn TRIP steel to improve strength and ductility. The results show that after twice cyclic quenching and ART exhibited optimum comprehensive properties, characterized by an ultimate tensile strength of 838 MPa, a total elongation of 90.8%, a product of strength and elongation (PSE) of 76.1 GPa·%, and the volume fraction of austenite of approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The investigation into the use of transformation-induced plasticity (TRIP)-assisted steels with multiphase microstructures has gained significant traction in developing durable but lightweight designs for vehicle body parts. [1][2][3][4][5] The genesis of TRIP steels can be traced back to Zackay et al 6 a discovery that paved the way for subsequent developments. Notably, Matsmura's breakthrough in 1987 revealed the allure of TRIP-assisted steels adorned with a composition of 50-60% allotropic ferrite, 20-30% bainitic ferrite without carbides, and highcontent retained austenite (RA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigation into the use of transformation-induced plasticity (TRIP)-assisted steels with multiphase microstructures has gained significant traction in developing durable but lightweight designs for vehicle body parts. [1][2][3][4][5] The genesis of TRIP steels can be traced back to Zackay et al 6 a discovery that paved the way for subsequent developments. Notably, Matsmura's breakthrough in 1987 revealed the allure of TRIP-assisted steels adorned with a composition of 50-60% allotropic ferrite, 20-30% bainitic ferrite without carbides, and highcontent retained austenite (RA).…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing facet of molybdenum was its capability to impede the formation of the pearlite phase within the microstructure. 3,30,31 In recent years, there has been a notable increase in scholarly investigations that have focused on exploring the possible beneficial effects of micro-alloy combinations such as Mo-Cr 15 and Mo-Ti. 32 An analysis conducted by Sugimoto et al 15 revealed that adding 0.2% Mo and 0.5% Cr resulted in a mixed structure of bainitic ferrite matrix and retained austenite, contributing to increased yield strength and improved mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to produce lightweight steels for vehicle bodies in response to simultaneously higher mechanical characteristics and lowered pricing [1][2][3][4], active research is being conducted on the TRIP-assisted steels that include multiphase microstructure. Zackay and colleagues [5] were the ones who made the discovery of transformation-induced plasticity (TRIP) steels, which is widely known.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high Mn content in medium manganese steel is prone to segregation, the high C content is not conducive to welding, the Al element will lead to continuous casting problems and cracking in the hot rolling process, and the addition of Si will cause difficulties with hot galvanizing and other application problems. Therefore, there is a considerable gap between actual industrial production and the application of middle manganese steels, especially those with ultra-high-strength [18,19].…”
Section: Introductionmentioning
confidence: 99%